Variability and trends of annual and seasonal thunderstorm frequency over Bangladesh. (29th February 2016) - Saha, Toma Rani; Quadir, Dewan Abdul
ABSTRACT: The climatology of thunderstorm (TS) activities over Bangladesh has been investigated using monthly, seasonal, and annual time series data of 29 meteorological stations in the country for a maximum period of 35 years (1976–2010). The climatology of the TS and its inter‐annual variability and trends have been investigated using country average as well as station‐wise data. The results of the trend analysis show that the country average TS frequency exhibits statistically significant trends for annual and seasonal data, except for winter. The monthly TS frequency shows significant increasing trends for the months April–November. The station‐wise analysis of annual and seasonal data shows dominant increasing trends over the country, with a few stations having negative trends. The correlation coefficients of the time series of seasonal and annual TS frequency with rainfall and minimum and maximum temperature have been computed. Also, the composite climatology of geopotential height and temperature fields of the troposphere covering Bangladesh and its surrounding areas for the month of May individually for the years with high TS frequency and low TS frequency has been presented and analysed. The low level moisture and meridional component of wind fields have also been considered. Additionally, the correspondence of TS frequency for this month with the low level vertical wind shear (VWS) between 850 and 500 hpa levels for the u ‐component of the wind has also been studied using the data of 1976–2010, which shows that the TS frequency is correlated with VWS.